New species and records of earthworms (Annelida, Oligochaeta: Crassiclitellata) in small holder farming systems in the Peruvian Amazon - Feijoo M., Alexander; Lavelle, Patrick (Zootaxa, 2023)
We examined external characters and internal anatomy, after dorsal dissection, of 11 species of Oligochaeta from the Peruvian Amazonia Loreto department. Four new species of families Glossoscolecidae and Rhinodrilidae and genera Righiodrilus and Martiodrilus are described here. Righiodrilus omagua, sp. nov., differs from other Righiodrilus by the presence of tubercula pubertatis in segments ½15, 15- ½18, 18; male pores located in intersegment 16/17; large seminal vesicles in segment 12 that extend until segment 24. Martiodrilus (Maipure) yurimaguensis, sp. nov., has a saddle-shaped clitellum in 14–1/4 25 and tubercula pubertatis between segments 1/318 –1/2 25. Martiodrilus (Maipure) tapiai, sp. nov., is differentiated from the others by the position of the tubercula pubertatis in 19–24, and the shape and size of spermathecae, common setae, ornamentation of genital setae and the location of male pores in intersegment 18/19. Martiodrilus (Martiodrilus) alegrei sp. nov., differs from other species of the genus by extension of tubercula pubertatis from 21 to 26, the number and shape of spermathecae. It is the only species of the genus that presents a single pair of spermathecae in segment 6. Additional records for the Peruvian Republic and the Amazonian region are also reported for Martiodrilus (Maipure) pano, Periscolex yuya, Pontoscolex (Pontoscolex) corethrurus, Rhinodrilus lavellei, Rhinodrilus pahanasii, Dichogaster (Diplothecodrilus) modiglianii and Ocnerodrilus occidentalis. With these new records, the earthworm fauna of Perú recorded so far increases to 36 species (21 native and 15 exotic), including eight native from Peruvian Amazonia Region. Many more species are still expected to be found.